Cyber Policy and Economics in an Internet Age - Lehr, William H.; Pupillo, Lorenzo; SpringerLink (Online service) (New York, NY : Springer US : Imprint: Springer, 2002)
Cyber Policy and Economics in an Internet Age is a collection of essays from some of the world's best-known experts on Internet public policy. It provides an accessible introduction to critical issues that policymakers, businesspeople, and the public will need to confront in coming years: universal access, appropriate content (pornography, free speech, cultural values), Internet broadcasting, intellectual property, Internet taxation, consumer protection, privacy, fair E-business competition, regulation of the Internet infrastructure, and more. This book is intended for the industry practitioner, analysts, and researchers. It would also be suitable for use in graduate and undergraduate courses, as well as by researchers.
1 Introduction -- 1. Living in an Internet Age -- 2 The Policy Challenge -- 2. The Three Digital Divides -- 3. Next Generation Internet: Where Technologies Converge and Policies Collide -- 4. Broadcasting Policy Hits the Internet -- 5. Globalization and the Internet Challenge -- 3 The Internet Governance Challenge -- 6. Names, Numbers, and Global Governance -- 7. Intellectual Property and the Information Economy -- 4 The Privacy Challenge -- 8. Protecting Privacy: The Canadian Experience -- 9. Economic Aspects of Personal Privacy -- 10. Cybercrimes v. Cyberliberties -- 5 The Economics Challenge -- 11. Implications of Electronic Commerce for Fiscal Policy -- 12. P2P, Digital Commodities, and the Governance of Commerce -- 13. Spectrum Allocation and the Internet -- Editors and Contributors -- Notes -- References.
Keywords: Public administration; Industrial organization; Information technology; Business$1 (BData processing.s; Business; Management science; Microeconomics; Public Administration; Industrial Organization; IT in Business; Business and Management, general; Microeconomics